Aligning Training and Client Expectations - Brenner, Michael (Association for Talent Development, 2014)
There are no promises that a training session will be a success; in fact, there most certainly will be some friction between a trainer and a client. This Infoline will explain how to approach the engagement with HEART - honesty, empathy, accountability, resiliency, and trustworthiness. --